Implementing Flash Card Learning Media to Improve Elementary School Students’ Learning Outcomes in Prayer Material - Zefrian Herwindika Pratama; Zubaedi Zubaedi (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: In Islamic education (PAI), particularly at the elementary level, students often find it challenging to engage with abstract or theoretical content, such as prayer material. Conventional lecture-based teaching methods tend to result in low motivation and limited knowledge retention. To overcome these issues, the use of innovative and interactive learning tools such as flashcards is being explored to enhance student comprehension and engagement. Objective This study aims to investigate the effectiveness of flashcard media in improving students’ learning outcomes in PAI, specifically on prayer-related material at SD Negeri 44 South Bengkulu. Method The research adopts a Classroom Action Research (CAR) approach, conducted during the 2023 academic year, focusing on fourth-grade students (N = 18). Data collection methods include observation, interviews, documentation, and tests. Results Analysis of test results across research cycles, measured against the Minimum Completeness Criteria (MCC), demonstrates a consistent improvement in student performance. Conclusion The implementation of flashcard media significantly enhances student engagement and learning outcomes in Islamic education, particularly in mastering prayer material. Contribution This study contributes to the advancement of innovative, student-centered learning strategies within Islamic education, offering practical insights for classroom implementation.